Knowledge, attitudes, and practices regarding legal and illegal substances by nursing students from Cartagena (Colombia) - Amparo Montalvo Prieto; Irma Yolanda Castillo ávila (Universidad de Antioquia, 2013)
Objective. This article sought to describe knowledge, attitudes, and practices regarding the use of legal and illegal substances by nursing students from Cartagena (Colombia). Methodology. This was a descriptive study conducted on a probabilistic sample of 689 students matriculated in three nursing programs. The study used the Predisposing Factors instrument associated to the use of psychoactive substances by Cepeda, Aldana, and Ossío. Results. The mean age of the participants was 20.5 years, 91.9% were women, 92.4% belonged to socio-economic levels 1 to 3, 87.5% were single. Of the 12 psychoactive substances (PAS) consulted, eight were considered by over 90% of the students as harmful to health. A total of 94% considered that the brain is the organ most affected by drug consumption. The students considered production (80.4%), trafficking (79.4%), and use of substances (80.0%) as problems of great importance; and they agreed with investing financial resources for prevention, rehabilitation, and follow-up programs for the population affected (89.1%). They expressed that use of PAS is mainly influenced by friends (26.9%) and by family problems (26.7%). The highest life prevalence of legal PAS use were: alcohol (77.6%) and cigarettes (17.6%); along with marihuana for illegal PAS use (1.8%). Conclusion. Knowledge of nursing students on legal and illegal PAS is not satisfactory, although they have favorable attitudes for their prevention and control. Use of PAS by the students, although not of great magnitude, is a problem deserving attention from organisms in charge of university welfare programs. Curricular contents should be enhanced on the phenomenon of PAS use of future nursing professionals.